2022
DOI: 10.1111/jpm.12823
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perspective about the Mental Health First Aid Training Programmes for adolescents in upper secondary schools: A focus group study

Abstract: Accessible Summary What is known on the subject? Mental Health First Aid Training Programmes with a pathogenic perspective are implemented worldwide for different participants and contexts. These interventions can promote the medicalization and psychiatrization movement of human suffering. Training programmes should teach about mental health nursing problems rather than disorders. However, there seem to be no studies describing these healthier interventions targeting adolescents in upper secondary schools. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…In particular: (1) the need for good coordination with the school in terms of short- and medium-term planning; (2) the importance of involving the adolescents themselves in the planning and implementation of the program, giving priority to their expressed needs, their opinions and active participation in decision-making, as well as the involvement of the school and parents/legal representatives; (3) the requirement for the facilitating team to undergo training prior to the implementation of the program; (4) the need to adopt inclusive and more protective measures in case there are adolescents with special health and educational needs, or non-native speaking adolescents or adolescents with mental health concerns; (5) the extreme importance of having a previously defined referral circuit for specialized care for the adolescents that the facilitators identify during the implementation of the program; and (6) the establishment of partnerships with some entities, for example, for the analysis of the data resulting from the evaluation instruments, but which may also be important in the context of the aforementioned specialized care for adolescents. These suggestions are consistent with several published works [ 2 , 7 , 9 , 33 , 36 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In particular: (1) the need for good coordination with the school in terms of short- and medium-term planning; (2) the importance of involving the adolescents themselves in the planning and implementation of the program, giving priority to their expressed needs, their opinions and active participation in decision-making, as well as the involvement of the school and parents/legal representatives; (3) the requirement for the facilitating team to undergo training prior to the implementation of the program; (4) the need to adopt inclusive and more protective measures in case there are adolescents with special health and educational needs, or non-native speaking adolescents or adolescents with mental health concerns; (5) the extreme importance of having a previously defined referral circuit for specialized care for the adolescents that the facilitators identify during the implementation of the program; and (6) the establishment of partnerships with some entities, for example, for the analysis of the data resulting from the evaluation instruments, but which may also be important in the context of the aforementioned specialized care for adolescents. These suggestions are consistent with several published works [ 2 , 7 , 9 , 33 , 36 ].…”
Section: Discussionsupporting
confidence: 94%
“…They suggested that it should have a modular format, with several sessions, every two weeks or every month, each session lasting between 45 and 90 min, using mainly active pedagogical methods, using pedagogical techniques such as role-play, games, group dynamics, discussion and reflection, among others, and eventually resorting to the use of technology, as long as it is very carefully selected so that it does not become an obstacle. These suggestions from the participants are consistent with the studies developed by other authors, namely Parnell et al [ 29 ], Morgado et al [ 9 , 30 ], Laranjeira & Querido [ 31 ], Choi et al [ 32 ] and Costa et al [ 33 ]. The contents were thoroughly discussed by all participants, and the consensus was that the Multifactor Model of Positive Mental Health factors should be addressed, that is, personal satisfaction, pro-social attitude, self-control, autonomy, problem solving and self-actualization, and interpersonal relationship skills.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, these interventions can improve recovery and decrease human damage. 10 Students of industrial training institutions (ITI) eventually go on to work in a variety of fields and industries and are subject to accidents. The most crucial thing to do when someone is harmed is to assist.…”
Section: Introductionmentioning
confidence: 99%